Tagged library for chemical genetics - Chang, Young-Tae (Henry Stewart Talks, 2008)
Chemical genetics is defined as "genetic" study using "chemical" tools, The key challenge in chemical genetics is target identification, Tagged library has been developed and demonstrated in this lecture to address the problem
Archived at 2020/08/13